A punção subaracnoidea sobre tatuagem determina alterções histológicas sobre o tecido nervoso e as meninges? - Ferraz, Isabela Leite [UNESP] (2014)
Body tattooing is part of many peoples culture in the world. Since 1990, it has been used as a body art. The tattoo pigments may contain organic and inorganic compounds, metals and solvents. The implications of performing regional anesthesia on tattooed skin are poorly known. There are no documented evidence or scientific proof that tattoo pigments can cause arachnoiditis or other neurological complications. Objectives: to assess whether spinal puncture performed on the tattooed skin of rabbits determine histological changes in the spinal nerve tissue and meninges. To analyze the presence of fragments of ink inside of needles. Methods: 36 rabbits were randomized in 3 groups (G). G1 puncture on tattoos, G2 spinal puncture on tattoos and injection of saline, G3 spinal puncture and injection of saline. The spinal puncture was ultrasound guided and performed under anesthesia in the space between the first and second sacral vertebra (a 22G 21/2 Quincke needle was used). The animals in the groups 2 and 3 received a 5 μl/cm spine volume solution (0,2 cc). The animals in the group 1 underwent only sacral puncture and, after that, was injected through the needle 1 cc of saline. The goal was to obtain histological material for conducting smear and possible identification of the tissue. The animals were evaluated clinically for 6 months. After this time they were sacrificed and have the lumbar and sacral portions of the spinal cord removed under anesthesia for histological examination by light microscopy. Results: pigments of ink was noted in all G1 smears material of needles. Perivascular lymphocytic infiltrate was noted in focal areas of the meninges in 33% of rabbits in group 2. Nervous tissue, meninges and blood vessels were normal in G3. Conclusion: subarachnoid puncture on the tattooed skin caused histological changes in the meninges, but not in the spinal nervous tissue. Fragments of tattoo ink were found inside of needles, despite the ...